PENYULUHAN KESEHATAN KEPADA MASYARAKAT DI DESA WONODADI DUSUN 03 TENTANG PENYAKIT KULIT - Diah Kartika Putri; Nadia Dwi Oktavian (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2023)
Wonodadi Village, there are still many people who throw garbage in the river, causing the well water around the residents to be contaminated with river water from community waste disposal. These unhealthy environmental conditions can trigger skin disease problems. This activity aims to solve problems that occur in the Wonodadi Village community with the extension method using assistance in the form of leaflets. This disease can be prevented by maintaining personal and environmental hygiene. Poor environmental conditions can result in many people being affected or infected with skin diseases. Based on the results of this counseling, it shows the enthusiasm of the community in knowing the causes, prevention and treatment of skin diseases. There were some people affected by skin diseases from the 40 people who attended. In this activity the community responds positively to the activities that have been carried out so that it runs well and smoothly.